Insects and other invertebrates in classical antiquity - Beavis, Ian C. (University of Exeter, 1988)
A comprehensive survey of insects and terrestrial invertebrates referred to by Greek and Roman authors from the earliest times to AD 600. Explains the extent and accuracy of their knowledge compared to current beliefs, and discusses the role of each animal type in classical life